Natural iron ores for large-scale thermochemical hydrogen and energy storage. (1st September 2022) - Bock, Sebastian; Pauritsch, Magdalena; Lux, Susanne; Hacker, Viktor
Highlights: Natural carbonate ores are promising for thermochemical hydrogen and energy storage. Cheap, abundant and environmentally friendly storage material. Large-scale energy storage in TWh-range. Thorough experimental analysis as basis for system design. Abstract: A stable energy supply will require balancing the fluctuations of renewable energy generation due to the transition to renewable energy sources. Intraday and seasonal storage systems are often limited to local geographical or infrastructural circumstances. This study experimentally verifies the application of inexpensive and abundant natural iron ores for energy storage with combined hydrogen and heat release. The incorporated iron oxides are reduced with hydrogen from electrolysis to store energy in chemically bonded form. The on–demand reoxidation releases either pure hydrogen or high-temperature heat as valuable products. Natural iron ores as storage material are beneficial as the specific costs are lower by an order of magnitude compared to synthetic iron oxide-based materials. Suitable iron ores were tested in TG analysis and in a 1 kW fixed-bed reactor. Siderite, a carbonate iron ore, was verified as promising candidate, as it shows significantly lower reaction temperatures and twice the storage capacity over other commercial iron ores such as ilmenite. The specific storage costs are as low as 80–150 $ per MWh hydrogen stored, based on the experimental in-situ tests. The experimentally determined volumetric energy storage capacity for the bulk material was 1.7 and 1.8 MWh m −3 for hydrogen and heat release, respectively. The raw siderite ore was stable for over 50 consecutive cycles at operating temperatures of 500–600 °C in in-situ lifetime tests. The combination of high abundance, low price and reasonable capacity can thus result in very low specific energy storage costs. The study proofs that suitable natural iron ores are an interesting economic solution for large-scale and seasonal energy storage systems.